الالتزام بضمان السلامة في عقد السياحة - بشينة، سميحة Bashinah, Samihah (جامعة زيان عاشور بالجلفة, 2018)
يعرف عقد السياحة بأنه اتفاق بين السائح ووكالة السياحة والسفر على أن تلتزم هذه الأخيرة بتقديم خدمة أو عدة خدمات مقابل ثمن يلتزم به السائح، ويترتب على انعقاده كغيره من العقود عدة التزامات تتحملها كل من وكالة السياحة والسفر والسائح، ويعد الالتزام بضمان السلامة من أهم الالتزامات تتحملها الوكالة، ويقصد به أن تلتزم وكالة السياحة والسفر بالمحافظة على سلامة السائح وسلامة أمتعته طوال مدة تنفيذ العقد. أما من حيث طبيعته فقد يكون أحيانا التزاما بتحقيق نتيجة وهي وصول السائح إلى بلد القيام سليما معافى وذلك في الرحلات السياحية الشاملة، كما قد يكون التزاما ببذل عناية لذلك في الرحلات الفردية التي تمارس فيها وكالة السياحة دور الوكيل في تقديم الخدمة للسائح. ويشترط فيه جملة من الشروط تتمثل أساسا في وجود خطر يهدد سلامة أحد المتعاقدين وأن يكون أمر الحفاظ على سلامة أحد المتعاقدين موكولا للمتعاقد الآخر وأخيرا أن يكون المدين بالالتزام محترفا. ويستمد هذا الالتزام وجوده من العقد الذي كان سببا في نشأته كما يستمد وجوده من ما هو من مستلزمات العقد كالقانون والعرف والعدالة. The contract of tourism is defined as an agreement between the tourist and the tourism and travel agency. The latter is obliged to provide a service or several services for a price charged by the tourist .The contract, like other contracts, entails several obligations borne by the travel agency and the tourist. Agency, and is intended to be committed to travel and travel agency to maintain the safety of the tourist and the safety of his luggage throughout the duration of the implementation of the contract .In terms of nature, it may sometimes be a commitment to achieve the result of a tourist’s arrival in a country to do well in comprehensive tourism trips ,and may be an obligation to take care in individual trips in which the agency plays the role of agent in providing service to tourists .A condition is stipulated, mainly, that there is a threat to the safety of a contractor, that the maintenance of the safety of a contractor is entrusted to the other contractor and finally that the debtor is professionally committed .This obligation derives from the existence of the contract which was the source of its inception and derives its existence from the requirements of the contract such as law, custom and justice.
Keywords: الخدمات السياحية -- الرحلات السياحية -- وكالات السفر والسياحة -- الالتزام بضمان السلامة -- القوانين والتشريعات